2020
DOI: 10.1159/000507026
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Uptake into the Vitreous after Peroral Coffee Consumption

Abstract: Introduction: Caffeine and its metabolites have antioxidant activity, scavenging reactive oxygen species. The aim of our study was to measure caffeine concentrations in vitreous samples after peroral caffeine intake. Methods: This prospective study included patients scheduled for 23-G pars plana vitrectomy with membrane peeling due to epiretinal membranes. The study was performed in two parts: in the first part, patients were recruited into three different groups: group A consisted of habitual coffee drinkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…Für diese retrospektive Analyse wurden Patientinnen und Patienten eingeschlossen, bei denen eine Pars-plana-Vitrektomie mit Membrane Peeling aufgrund von iERM an der Augenabteilung des Hanusch-Krankenhauses Wien, Österreich, durchgeführt wurde im Zeitraum zwischen Mai 2014 und August 2019. Die Patientinnen und Patienten wurden aus 6 prospektiven Studien ausgewählt 9 , 24 , 25 , 26 , 27 , 28 und in die Analyse inkludiert, wenn sie folgende Einschlusskriterien erfüllt haben: a) Vorhandensein einer iERM, b) Indikation für das Membrane Peeling – diese wurde durch einen signifikanten Visusabfall und/oder Metamorphopsien durch die iERM definiert, und c) pseudophaker Linsenstatus zum Zeitpunkt 3 Monate postoperativ. Patientinnen und Patienten mit Makulaödem, das durch andere Augenerkrankungen als iERM verursacht wurde, wurden von der Studie ausgeschlossen.…”
Section: Methodenunclassified
See 1 more Smart Citation
“…Für diese retrospektive Analyse wurden Patientinnen und Patienten eingeschlossen, bei denen eine Pars-plana-Vitrektomie mit Membrane Peeling aufgrund von iERM an der Augenabteilung des Hanusch-Krankenhauses Wien, Österreich, durchgeführt wurde im Zeitraum zwischen Mai 2014 und August 2019. Die Patientinnen und Patienten wurden aus 6 prospektiven Studien ausgewählt 9 , 24 , 25 , 26 , 27 , 28 und in die Analyse inkludiert, wenn sie folgende Einschlusskriterien erfüllt haben: a) Vorhandensein einer iERM, b) Indikation für das Membrane Peeling – diese wurde durch einen signifikanten Visusabfall und/oder Metamorphopsien durch die iERM definiert, und c) pseudophaker Linsenstatus zum Zeitpunkt 3 Monate postoperativ. Patientinnen und Patienten mit Makulaödem, das durch andere Augenerkrankungen als iERM verursacht wurde, wurden von der Studie ausgeschlossen.…”
Section: Methodenunclassified
“…This retrospective analysis included patients scheduled for pars plana vitrectomy with membrane peeling for an iERM between May 2014 and August 2019 at the Department of Ophthalmology at the Hanusch Hospital in Vienna, Austria. Patients were selected from six prospective studies 9 , 24 , 25 , 26 , 27 , 28 and included for analysis in cases where they fulfilled the following inclusion criteria: a) presence of an iERM, b) indication for membrane peeling, defined as a significant loss of visual acuity and/or metamorphopsia due to the iERM, and c) pseudophakia at the final visit at 3 months after surgery. Patients with macular edema caused by conditions other than an iERM were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…One study showed that air tamponade did not result in significantly more postsurgical tilt of the intraocular lens in case of phacovitrectomy [32], 1 study examined Fourier transform infrared spectroscopy imaging of ERM [unpubl. data], 1 study examined the role of intraoperative OCT during peeling without staining [33], and 1 study examined concentrations of caffeine in vitreous, ERM, and blood serum samples [34]. As none of these studies evaluated the role of phacoemulsification on postsurgical results, we performed a retrospective analysis including patients from these studies who fulfilled the above-mentioned inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%